Influência de diferentes clarificantes proteicos no vinho 'merlot' da região da campanha gaúcha - Pinto, Rayssa Marçal (2017)
Brazil has presented significant growth in the wine sector due to favorable climate and soil conditions, with severe winters and hot dry summers and a good thermal amplitude, which gives the grape a good maturation and phenolic compounds, consequently a product of high quality. There are several states and regions that produce grapes, but it is mainly concentrated in Rio Grande do Sul. The Campanha Gaúcha is the second largest wine producing region in Brazil, only behind the Serra Gaúcha. The cultivar Merlot of the species Vitis vinifera can be considered as a cultivar originating in Medoc, France, where it was already cultivated in 1859, expanding to other regions of France and to many other wine grower countries. The purpose of the clarification process is to clarify, stabilize and improve the organoleptic characteristics of both white and red wines. It is one of the most common activities in the winemaking process. The objective of this work was to evaluate the effect of the clarification process of the 'Merlot' red wine, produced in the Gaúcha Campaign region, using different types of protein clarifiers (Albumin, liquid gelatine, vegecoll, phytochemical and catalase), average and maximum recommended by manufacturers. The experiment was carried out at the Federal University of Pampa - Campus Dom Pedrito, in the experimental winery, where a Merlot red wine, vintage 2016, was made with grapes from a vineyard in the municipality of Bagé- RS. Thirty days after the packaging, physicochemical analyzes of the wines were performed to evaluate the effect of the clarifiers on the phenolic composition. The results show that there was a significant difference in the majority of the analyzes performed. Plant proteins cause significant reduction of anthocyanins. However, the clarifier derived from the potato was the one that had the best result in the gelatine index that gives the percentage of tannins able to react with the proteins, that is, it was the wine that theoretically presented an ideal body and astringency. The total polyphenol index obtained a minimum recommended value in most treatments. The turbidity ranged from 12 to 32 NTU, and for wine to be considered clear it has to be less than 8 NTU. This is because the wines do not go through the filtration process. The results presented are all within the standard of identity and quality established by the current legislation and none of the treatments presented alteration that could be considered a defect, or failure in winemaking. The vegetable based clarifiers showed results similar to those already used in oenology. Therefore, further studies are needed to prove their efficiency so that they can later substitute clarifiers of animal origin.